2017
DOI: 10.3390/geosciences7040116
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Tsunami Evacuation Maps at Setubal Municipality, Portugal

Abstract: Abstract:The Setubal municipality, Portugal, has diversified land use along its coastline (mostly located in a low-lying area): on the west there are beaches; the centre is dominated by a densely populated downtown; and the east has an important industrial area. Although the seismic activity in mainland Portugal is moderate, considering the variety of exposed elements, the objectives of this study are to present and discuss the implementation of tsunami evacuation maps at Setubal municipality. Thus, tsunami nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 23 publications
1
27
0
Order By: Relevance
“…The authors were able to validate the tsunami initial response, which was the subsidence at Cadiz, Spain and Morocco, as reported by the witnesses. The authors also validated most of the travel times reported by the witnesses, and tsunami water level waveforms in the UK; f) numerical modeling of the 1755 tsunami carried out at the local scale on several Portuguese coastal areas allowed researchers to calculate the tsunami inundation, reproducing tsunami travel times and local tsunami features such as the number of waves, inundation extension, and run-up [17,[26][27][28]. As a consequence, in this study, the tsunami source area will be considered at the Gorringe Bank, with the source parameters used by [11,17,[25][26][27][28].…”
Section: Review Of the Seismo-tectonics Offshore Of The Portuguese Mamentioning
confidence: 70%
See 4 more Smart Citations
“…The authors were able to validate the tsunami initial response, which was the subsidence at Cadiz, Spain and Morocco, as reported by the witnesses. The authors also validated most of the travel times reported by the witnesses, and tsunami water level waveforms in the UK; f) numerical modeling of the 1755 tsunami carried out at the local scale on several Portuguese coastal areas allowed researchers to calculate the tsunami inundation, reproducing tsunami travel times and local tsunami features such as the number of waves, inundation extension, and run-up [17,[26][27][28]. As a consequence, in this study, the tsunami source area will be considered at the Gorringe Bank, with the source parameters used by [11,17,[25][26][27][28].…”
Section: Review Of the Seismo-tectonics Offshore Of The Portuguese Mamentioning
confidence: 70%
“…It is the origin of the M s = 8.0 earthquake occurred in 28 February, 1969 ( Figure 4). This was the highest instrumental earthquake event in the Iberia-Morocco-Atlantic domain [11,17].…”
Section: Review Of the Seismo-tectonics Offshore Of The Portuguese Mamentioning
confidence: 91%
See 3 more Smart Citations